2022
DOI: 10.3390/toxins14050318
|View full text |Cite
|
Sign up to set email alerts
|

Six Main Contributing Factors to High Levels of Mycotoxin Contamination in African Foods

Abstract: Africa is one of the regions with high mycotoxin contamination of foods and continues to record high incidences of liver cancers globally. The agricultural sector of most African countries depends largely on climate variables for crop production. Production of mycotoxins is climate-sensitive. Most stakeholders in the food production chain in Africa are not aware of the health and economic effects of consuming contaminated foods. The aim of this review is to evaluate the main factors and their degree of contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 151 publications
1
20
0
1
Order By: Relevance
“…It was found that the focus of the work of the Food Safety Administrative Agency in China currently was the investigation into counterfeit and low-quality products such as poisoned rice and counterfeit edible oil [ 26 ]. However, people pay little attention to the detection of the internal composition and content of food, which is the key to understanding whether the food contains toxins, especially aflatoxin.…”
Section: Result Analysis and Discussionmentioning
confidence: 99%
“…It was found that the focus of the work of the Food Safety Administrative Agency in China currently was the investigation into counterfeit and low-quality products such as poisoned rice and counterfeit edible oil [ 26 ]. However, people pay little attention to the detection of the internal composition and content of food, which is the key to understanding whether the food contains toxins, especially aflatoxin.…”
Section: Result Analysis and Discussionmentioning
confidence: 99%
“…Furthermore, production of mycotoxins is climate-sensitive where weather and climate variables increases high susceptibility to mycotoxin contamination in Africa. One of the continents with high mycotoxin contamination of foods and remains at record high with incidences of liver cancer globally is Africa (Nji et al, 2022). In addition, climatic factors influence fungal occurrence, such as high temperature and humidity, influence fungal occurrence, thereby increasing the risk of fungal growth and mycotoxin production.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, consumers’ exposure to mycotoxins is potentially higher in rural communities when compared to those in cities and towns due to higher levels of maize intake, and higher levels of dietary mycotoxin loads. In addition, subsistence farming practices and pre-harvest (improper management of residue or debris from previous harvests, which contain fungal spores and can increase systemic infection, inappropriate cultivar and use of fertiliser) and post-harvest (unconventional and unhygienic drying techniques as well as traditional or crude storage techniques) handling of crops provide conducive environments for fungal development and mycotoxin production [ 40 ].…”
Section: Possible Sources Of Mycotoxin Exposure To Humans and Animalsmentioning
confidence: 99%
“…There are different types of beers brewed from cereals in South Africa, and for socio-cultural reasons, mouldy maize is used intentionally in the Eastern Cape and Limpopo to brew beer as it is believed to improve flavour [ 68 , 69 ]. The cereals used are mostly from subsistence farming, which are most often highly contaminated with mycotoxins as a result of poor pre- and post-harvest handling [ 40 ]. The fates of most locally brewed beers with regard to mycotoxin content in SA are yet to be determined.…”
Section: Possible Sources Of Mycotoxin Exposure To Humans and Animalsmentioning
confidence: 99%